Analysis of initial stabilization of cell efficiency in amorphous silicon photovoltaic modules under real outdoor conditions. (May 2018) - Mateo, C.; Hernández-Fenollosa, M.A.; Montero, Á.; Seguí-Chilet, S.
Abstract: This contribution presents a field study in which the initial stabilization of thin-film amorphous silicon (a-Si:H) is investigated. Two grid-connected a-Si:H photovoltaic plants have been monitored and analyzed under real outdoor conditions. A per-unit approach is proposed to compare PV plants with differences in their electrical characteristic and the start-up date. The representation of a normalized per-unit PV power versus the accumulated incoming irradiation reveals an evolution that can be characterized through an exposure-response function. By this function, two populations of defects in the cells are detected. It is found that the stabilization process in the first year of operation produces a decrease of 10% in the peak power, equivalent to a decrease of 0.5% in cell efficiency. The use of the accumulated PSH for conducting the analysis of the initial stabilization produces similarities that cannot be obtained if a time scale is used. These results provide a powerful tool for PV plant designers because they enable a prediction to be made of the time-scale stabilization response in terms of unitary power, correlated with the peak sun hours received. Graphical abstract: Image 1 Highlights: PV efficiency stabilization in a-Si:H modules by means of dose-response function. Dependency of defect populations with the accumulated irradiation. Different seasonal effects after initial stabilization depending on the starting date. Normalization approach to compare different a-Si PV plants. Cell efficiency comparison using flash-report data and experimental values.